1996
DOI: 10.1111/j.1365-2044.1996.tb07798.x
|View full text |Cite
|
Sign up to set email alerts
|

Does post‐laparoscopy pain relate to residual carbon dioxide?

Abstract: Forum 485Although we have demonstrated statistically significant differences in both blood loss and contraction of the uterus between the syntocinon and saline groups, we d o not think that this difference is clinically significant since the amount of blood loss was quite small. Syntocinon is not devoid of side effects when given as a bolus intravenous injection; it causes vasodilatation with transient hypotension and reflex tachycardia, which may be tolerated well in young healthy women, but may be hazardous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
1
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(132 citation statements)
references
References 2 publications
2
109
1
15
Order By: Relevance
“…El dolor postcolecistectomía en la cirugía laparoscópica parece estar provocado por el neumoperitoneo, por lo que se recomienda trabajar a bajas presiones de CO2, así como la completa expulsión del gas antes de cerrar los orificios de los trócares (13,14,15).…”
Section: Discussionunclassified
“…El dolor postcolecistectomía en la cirugía laparoscópica parece estar provocado por el neumoperitoneo, por lo que se recomienda trabajar a bajas presiones de CO2, así como la completa expulsión del gas antes de cerrar los orificios de los trócares (13,14,15).…”
Section: Discussionunclassified
“…It is thought that pneumoperitoneum causes diaphragmatic irritation by overstretching the diaphragmatic muscle fibres resulting in a pain sensation mediated by the phrenic nerve [23]. Jackson et al investigated the association between the dimension of the gas bubbles in the peritoneal cavity and the severity of pain and found a correlation between the residual gas volume and post-laparoscopic pain [23]. To support the theory of overstretched diaphragmatic muscle fibres, it has also been shown that low insufflation rate reduces post-operative SP [24].…”
Section: Discussionmentioning
confidence: 99%
“…As far shoulder pain in laparoscopic procedure though precise reason is unclear, but leading hypothesis is that CO 2 introduced in abdomen cause phrenic nerve irritation causing referred pain to C4 segment [8]. Prolonged presence of shoulder tip pain suggests excitation of phrenic nerve [9].…”
Section: Introductionmentioning
confidence: 99%